New colored reactions for research combination analysis carbonyls of biochemical interest (Revista Española de Fisiología, 1974)
As consequence of previous studies with the bisulphite compound of trimethoxydioxyfucsone, we describe news coloured reactions of anothers carbonilic groups more actives, based in their-capacity of actuation upon the same, liberating the initial quinonic structure, one’s own of this colouring matter, with the consequent regeneration of the characteristic colour.News similar reactives of carbonilic group are proposed, extending this type of reactions to the red form of phenolphthaleine, which enables the easy disponibility of the corresponding reactive in the laboratory.A new technics of obtainment of the trimethoxydioxyfucsone is described with a general critical about the posibilities of application of the above mentioned type of coloured reactions to the investigations reported with the molecular structure by means of photometric technics of the kinetic chemistry and to the establishment of colourimetric micromethods for the quantitative estimation of carbonilic compounds of biochemical interest.